Analisa dan Pengembangan Modul Berbasis RFID pada Aplikasi UMB Mobile - Ranggadara, Indra; Pratama, Wahyu; Rahmawati, Dita Baitu (Jurnal Ilmiah FIFO, 2019)
Presence is significant for every lecture, office or other organizational activities, currently recording the attendance of student lectures at Mercu Buana University by calling one student at a time to be present by the lecturer, then the lecturer giving a sign of attendance on the particular lecturer application form that has provided. The purpose of this study is to analyze and develop RFID-based mobile UMB, which has the benefit of students being able to attend their presence without having to wait for lecturers to attend the attendance process and students can find out the level of time delay so that it can become learning so as not to delay in the future. The method used in this study uses a SWOT analysis and then designed with a system using UML, the construction of this application using the Waterfall method, and testing using a BlackBox. The results of this study are the development of modules in the UMB Mobile application successfully implemented with RFID devices.